2021
DOI: 10.1186/s12889-021-12216-3
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Perceptions and Experiences of Breastfeeding: a scoping review of the literature

Abstract: Background Despite public health efforts to promote breastfeeding, global rates of breastfeeding continue to trail behind the goals identified by the World Health Organization. While the literature exploring breastfeeding beliefs and practices is growing, it offers various and sometimes conflicting explanations regarding women’s attitudes towards and experiences of breastfeeding. This research explores existing empirical literature regarding women’s perceptions about and experiences with breast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Half of the participants described feeling honored to do whatever needed to be done to breastfeed and support their infants’ emotional and physical health, which is consistent with previous literature (Beggs et al, 2021; Jackson et al, 2019). A scoping review conducted by Beggs et al (2021) revealed the perceptions that “breast is best” and “breastmilk is best” were consistent motivations of mothers in their infant feeding choices. Breastfeeding helped the participants in the present study to combat some of the intrapersonal stigma they felt as a mother receiving MOUD.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Half of the participants described feeling honored to do whatever needed to be done to breastfeed and support their infants’ emotional and physical health, which is consistent with previous literature (Beggs et al, 2021; Jackson et al, 2019). A scoping review conducted by Beggs et al (2021) revealed the perceptions that “breast is best” and “breastmilk is best” were consistent motivations of mothers in their infant feeding choices. Breastfeeding helped the participants in the present study to combat some of the intrapersonal stigma they felt as a mother receiving MOUD.…”
Section: Discussionsupporting
confidence: 87%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. (Beggs et al, 2021;Jackson et al, 2019). A scoping review conducted by Beggs et al (2021) revealed the perceptions that "breast is best" and "breastmilk is best" were consistent motivations of mothers in their infant feeding choices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as insufficient maternal leave, lack of training from hospitals, maternal diseases and psychological problems, etc. discourage the practice of exclusive breastfeeding [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A woman’s decision to breastfeed is a process influenced by a myriad of factors which will determine both the initiation of breastfeeding, and the resilience allows for its maintenance in the face of adversities which may come about in a process that is generally idealized [ 9 ]. Despite being a personal decision, the woman will draw on all sources of experience and role models from everyone who is around her in order to choose one option or another [ 10 ].…”
Section: Introductionmentioning
confidence: 99%